(untitled) (Medico Legal Update, 2021)
Globalization, which has now crossed the line, has had many impacts on all countries in the world including Indonesia. One of the impacts of globalization is the impact of deviant associations such as LGBT and it affects various countries. The emergence of the LGBT phenomenon, which is currently a hot topic of discussion by various parties in Indonesia, has raised pros and cons views on the legality of LGBT in society. LGBT legalization in various countries is currently encouraging LGBT survivors in Indonesia to urge the government to legalize LGBT. Therefore, this article will discuss the reality of LGBT and its legal arrangements in Indonesia and how to analyze the philosophy of law on the reality of LGBT in Indonesia. The results of the study show that according to the constructivism paradigm in the contextual review of legal philosophy in Indonesia, LGBT is not in accordance with the values of Pancasila as the nation’s life guide.